Applications of Vygotskyan concept of mediation in SLA - Guerrero Nieto, Carmen Helena (Colombian Applied Linguistics Journal, 2007)
The application of Vygotskian ideas is not new to education, research studies abound reporting various ways in which they can be applied. But in the particular field of Second Language Acquisition a Vygotskian approach is rather new, with the first studies dating from about mid 1990s. In this article I discuss one Vygotskian concept, mediation, and report on some research studies that have been framed in this concept. I found that the studies surveyed could be grouped according to the type of mediation, therefore three categories emerged: Mediation by dialoguing with one self, Mediation by dialoguing with the other, and mediation through technology.